INFLUENCE OF GOOD CORPORATE GOVERNANCE, LEVERAGE AND COMPANY SIZE ON FINANCIAL PERFORMANCE IN MANUFACTURING COMPANIES LISTED ON THE IDX IN 2017-2021 - Sumarni; Eka Rizky Pradiyatni Pratiwi; Mauzu, Fahrul; Mahmud (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
This research aims to determine the effect of good corporate governance, leverage, and company size on the financial performance of manufacturing companies listed on the IDX in 2017-2021. Where good corporate governance is proxied to the board of commissioners, independent commissioners and managerial ownership, variable leverage, and company size. The samples used in this research were 32 manufacturing companies with certain criteria with a total sample data of 160. The sampling technique used was purposive sampling method and analyzed using multiple linear regression tests using the SPSS 21 program. The results of this research partially show that the board of commissioners, independent commissioners and managerial ownership as well as leverage variables have significant and significant effects on financial performance while the company variable size has no significant effect on financial performance. Then simultaneously the overall variables namely the board of commissioners, independent commissioners, managerial ownership, leverage and company size state that the independent variables together have an influence and are significant on the financial performance of manufacturing companies listed on the Indonesian Stock Exchange (IDX) in 2017-2021